Zur Bedeutung der Balance verschiedener Lernarrangements für inklusiven Mathematikunterricht in der Grundschule (mathematica didactica, 2021)
This article explores the role and relation of different learning situations for inclusive mathematics education in primary schools. For this purpose, theoretical research on inclusive didactics and mathematics education is discussed together with the empirical findings of narrative semi-structured interviews with children, parents, researchers, primary school and special education teachers. Findings indicate that a balance of different learning situations is needed for successful inclusive learning of mathematics.